Carbon-coated silicon-based negative electrode material and preparation method thereof

The soluble organic carbon source is coated on nanosilicon particles by spray granulation to form a silicon core-carbon shell structure, which solves the problem of volume expansion and poor conductivity of the silicon-based negative electrode material, and improves the first effect and stability of the battery.

CN119674022APending Publication Date: 2025-03-21SICHUAN CHANGHONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895045.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The theoretical capacity of traditional graphite negative electrode materials is low, and silicon-based negative electrode materials have problems such as large volume expansion and poor conductivity, resulting in rapid attenuation and failure of battery capacity.

Method used

The soluble organic carbon source and nanosilicon particles are coated by spray granulation to form a core-shell structure of a silicon core-carbon shell cladding layer through which long chain carbon is penetrated.

Benefits of technology

It effectively solves the problems of volume expansion and poor conductivity of silicon-based negative electrode materials, and improves the first-effect and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201513740000081
    Figure BDA0005201513740000081
  • Figure HDA0005201513750000011
    Figure HDA0005201513750000011
  • Figure HDA0005201513750000021
    Figure HDA0005201513750000021
Patent Text Reader

Abstract

The invention discloses a carbon-coated silicon-based negative electrode material and a preparation method thereof, and relates to the technical field of preparation of negative electrode materials. The preparation method sequentially comprises the following steps: in an inert atmosphere, putting silicon powder and a grinding aid into a grinding solvent, and grinding to obtain nano silicon slurry; then adding a nano dispersant, uniformly stirring and mixing, adding a long-chain resin material, and uniformly stirring; carrying out spray granulation, placing in an inert atmosphere, and calcining to obtain a coating precursor with chain-like resin penetrating through the nano silicon particles; and adding the coated precursor into the nano silicon slurry, adding liquid asphalt, uniformly stirring, carrying out secondary spray granulation, placing in an inert atmosphere, calcining, crushing and grading to obtain the carbon-coated silicon-based negative electrode material. According to the invention, the soluble organic carbon source and the nano silicon particles are coated by a spray granulation method to obtain a core-shell structure of a long-chain carbon penetrating silicon core-carbon shell coating layer, so that the problems of volume expansion, poor conductivity and the like of the existing silicon-based negative electrode material are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode material preparation, and in particular to a carbon-coated silicon-based negative electrode material and a preparation method thereof. Background Art

[0002] With the rapid growth of demand for energy storage batteries for small mobile devices and new energy vehicles, the theoretical capacity of traditional graphite negative electrode materials is low (only 372mAh / g), and the actual commercialized graphite material capacity is almost close to its theoretical value (up to 372mAh / g or more), which has gradually become difficult to meet the rapidly growing new energy vehicle market, causing electric vehicles to enter a period of range anxiety. Among the many negative electrode materials with high energy density potential in the next generation, silicon materials have advantages such as ultra-high theoretical capacity (4200mAh / g) and stable chemical properties, low cost, high abundance, safety and non-toxicity. However, there are limitations of silicon negative electrodes that cannot be ignored: large volume expansion rate (about 300%) and weak conductivity. Huge volume expansion can cause the material to pulverize or even detach from the current collector, resulting in rapid capacity decay and accelerated battery failure. At the same time, the repeatedly generated solid electrolyte interface (SEI) film will also consume a large amount of lithium ions, further causing battery failure. Low conductivity makes it difficult for lithium ions to migrate into the interior of the material for alloying reactions, and they remain in the electrode material. The irreversible consumption of lithium ions causes the battery's initial coulombic efficiency to be low.

[0003] In response to the above-mentioned problems, the main technical routes in the industry can be specifically divided into three major technical routes: silicon-oxygen composite, silicon-carbon composite and silicon-based alloy. Among them, the silicon-carbon negative electrode is usually composed of a mixture of nano-silicon and graphite materials. By reducing the particle size of the silicon-based material to the nanometer level, a smaller particle size and more voids can be obtained, which makes it easier to buffer the stress and deformation generated by silicon in the process of lithium ion extraction. In addition, nanoparticles can shorten the diffusion distance of lithium ions and increase the lithium storage capacity of silicon materials. The core difficulty of the production process of silicon-carbon negative electrode lies in the preparation of nano-silicon powder and the coating of carbon materials. Carbon coating methods mainly include solid phase coating, liquid phase coating and CVD gas phase coating. However, there are many problems with the above three coating methods: such as the solid phase coating process is mature and easy to mass produce, but the coating effect is difficult to control and the coating uniformity is poor; the coating effect of liquid phase coating is more uniform, but the selectivity of its soluble coated carbon material is limited; gas phase coating can achieve uniform coating, but on the basis of existing technology, there are equipment limitations in large-scale production, high cost, and higher process risk factor. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon-coated silicon-based negative electrode material and a preparation method thereof, which uses a soluble organic carbon source and nano-silicon particles for coating through a spray granulation method to obtain a core-shell structure of a silicon core-carbon shell coating layer with long-chain carbon running through it, effectively solving the problems of volume expansion and poor conductivity of existing silicon-based negative electrode materials.

[0005] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a carbon-coated silicon-based negative electrode material is provided, which comprises the following steps in sequence:

[0006] (1) In an inert atmosphere, place micron-sized silicon powder and grinding aid in a grinding solvent and grind to D 50 ≤50nm, nano silicon slurry is obtained;

[0007] (2) adding a nano-dispersant to the nano-silicon slurry, stirring and mixing, and then adding a long-chain resin material soluble in a grinding solvent, stirring evenly;

[0008] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500-1100° C. for 2-5 hours under an inert atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0009] (4) Add the coated precursor to a nano-silicon slurry diluted with a grinding solvent to a solid content of 5-20%, then add 18-50wt% of liquid asphalt, stir evenly, spray granulate for a second time, and then place it in an inert atmosphere and calcine it at 500-1100°C for 2-5h. After crushing, grade it to obtain a carbon-coated silicon-based negative electrode material.

[0010] Furthermore, in step (1), the mass volume ratio of silicon powder, grinding aid and grinding solvent is 1000g:100g:5.5L.

[0011] Furthermore, in step (1), the grinding aid is at least one of lignin, gallic acid, tannic acid carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, gum arabic, gelatin and guar gum.

[0012] Furthermore, in step (2), the mass ratio of the nano-dispersant to the long-chain resin material is 10 g:150 g.

[0013] Furthermore, in step (2), the nanodispersant is at least one of DP-8300, F-601, polyvinyl pyrrolidone and sodium dodecyl sulfate.

[0014] Furthermore, in step (2), the long-chain resin material is at least one of acrylic resin, phenolic resin, polyvinyl butyral resin, polyurethane resin and natural resin.

[0015] Furthermore, in step (3) and step (4), spray granulation is carried out at a temperature of 80-170°C.

[0016] Further, in step (4), after crushing, the crushed 50 8-15μm.

[0017] Furthermore, in step (1) and step (4), the grinding solvent is at least one of ethanol, ethylene glycol and propylene glycol.

[0018] The present invention also provides a carbon-coated silicon-based negative electrode material prepared by the method for preparing the carbon-coated silicon-based negative electrode material.

[0019] The present invention has the following beneficial effects:

[0020] 1. The present invention coats the soluble organic carbon source and nano silicon particles by spray granulation to obtain a core-shell structure of a silicon core-carbon shell coating layer. The silicon core formed by the aggregation of nanoparticles can reduce the stress between the particles, and the carbon coating layer wraps the silicon particles to avoid direct contact with the electrolyte, forming a uniform carbon shell layer in the liquid phase, and forming a uniform SEI film on the surface after reacting with the electrolyte.

[0021] 2. The present invention adopts a coating method of secondary spray granulation and sintering, and the particle structure of the obtained secondary coated composite negative electrode material is as follows Figure 1 As shown; the first time, long-chain resin is used, which can penetrate between nano-silicon particles and enhance internal conductivity after calcination; the second time, liquid asphalt is used, which can achieve a more uniform coating on the surface of the precursor.

[0022] 3. The organic carbon source introduced in the present invention is a long-chain branched structure for the first time, which can penetrate between nano silicon particles during the spray granulation process and form a conductive network between silicon particles after sintering into carbon. The second spray drying uses liquid asphalt for surface carbon coating. Compared with the traditional solid asphalt high-temperature melting carbon coating method, the liquid asphalt plus spray drying method makes the coating layer more uniform and can achieve low-temperature coating. In short, the carbon coating by the liquid phase coating method using spray drying can provide multiple choices of organic carbon sources, flexible design of the particle structure, and achieve uniform coating with adjustable carbon coating amount.

[0023] 4. Silicon-carbon composite materials with core-shell structure wrap silicon particles in a carbon layer, which can effectively prevent direct contact between silicon and electrolyte, reduce the formation of SEI film, and improve the first effect; while silicon-carbon composite materials with uniform dispersion structure can give full play to the synergistic effect of silicon and carbon, and improve the conductivity and stability of the electrode. Through the spray-sintering secondary granulation method, the structure of the organic carbon source used is selected, and the structure of the skeleton of the entire particle is regulated, so that the core can have long-chain conductive carbon running through the silicon particles, and the surface has a uniformly coated carbon layer, which can effectively improve the first effect of the silicon-carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of the structure of carbon-coated silicon-based negative electrode material particles obtained in the present invention;

[0025] Figure 2 This is a morphology picture of particles after secondary spray granulation and classification after crushing in Example 1. DETAILED DESCRIPTION

[0026] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0027] Example 1

[0028] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0029] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g lignin were mixed in 5.5L grinding solvent (ethanol) and ground to D 50 ≤50nm, nano silicon slurry is obtained;

[0030] (2) Add 10 g of nano-dispersant (DP-8300) to the nano-silicon slurry, stir and mix, then add 150 g of phenolic resin soluble in the grinding solvent, and stir evenly;

[0031] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0032] (4) 1000 g of the coated precursor was added to a nano-silicon slurry diluted to a solid content of 5% by grinding solvent, and then 30 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 800 ° C for 5 h, and crushed and graded to D 50The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0033] Example 2

[0034] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0035] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g tannic acid were placed in 5.5L grinding solvent (ethanol) and ground with a sand mill to D 50 ≤50nm, nano silicon slurry is obtained;

[0036] (2) Add 10 g of nano-dispersant (F-601) to the nano-silicon slurry, stir and mix, then add 150 g of acrylic resin soluble in the grinding solvent and stir evenly;

[0037] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 550° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0038] (4) 1000 g of the coated precursor was added to a nano-silicon slurry diluted to a solid content of 5% by grinding solvent, and then 25 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 750 ° C for 5 h, and crushed and graded to D 50 The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0039] Example 3

[0040] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0041] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g gallic acid were placed in 5.5L grinding solvent (ethanol) and ground with a sand mill to D 50 ≤50nm, nano silicon slurry is obtained;

[0042] (2) Add 10 g of nano-dispersant (F-601) to the nano-silicon slurry, stir and mix, then add 150 g of polyvinyl butyral resin soluble in the grinding solvent, and stir evenly;

[0043] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0044] (4) 1000 g of the coated precursor was added to a nano-silicon slurry diluted to a solid content of 10% by grinding solvent, and then 20 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 750 ° C for 5 h, and crushed and graded to D 50 The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0045] Example 4

[0046] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0047] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g sodium alginate were placed in 5.5L grinding solvent (ethanol) and ground with a sand mill to D 50 ≤50nm, nano silicon slurry is obtained;

[0048] (2) Add 10 g of nano-dispersant (polyvinyl pyrrolidone) to the nano-silicon slurry, stir and mix, then add 150 g of polyurethane resin soluble in the grinding solvent and stir evenly;

[0049] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0050] (4) 1000 g of the coated precursor was added to the nano-silicon slurry diluted to a solid content of 12% by grinding solvent, and then 18 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 750 ° C for 5 h, and crushed and graded to D 50 The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0051] Example 5

[0052] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0053] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g polyvinyl alcohol and tannic acid (1:1) were placed in 5.5L grinding solvent (ethanol) and ground with a sand mill to D 50 ≤50nm, nano silicon slurry is obtained;

[0054] (2) Add 10 g of nano-dispersant (sodium dodecyl sulfate) to the nano-silicon slurry, stir and mix, then add 150 g of natural resin soluble in the grinding solvent, and stir evenly;

[0055] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0056] (4) 1000 g of the coated precursor was added to a nano-silicon slurry diluted to a solid content of 10% by grinding solvent, and then 20 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 750 ° C for 5 h, and crushed and graded to D 50 The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0057] Example 6

[0058] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0059] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g of gum arabic and gelatin (1:1) were placed in 5.5L grinding solvent (ethanol) and ground with a sand mill to D 50 ≤50nm, nano silicon slurry is obtained;

[0060] (2) Add 10 g of nano-dispersant (DP-8300 and F-601 mixed in a mass ratio of 1:1) to the nano-silicon slurry, stir and mix, then add 150 g of phenolic resin soluble in the grinding solvent, and stir evenly;

[0061] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0062] (4) 1000 g of the coated precursor was added to the nano-silicon slurry diluted to a solid content of 10% by grinding solvent, and then 30 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 750 ° C for 5 h, and crushed and graded to D 50 The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0063] Example 7

[0064] A carbon-coated silicon-based negative electrode material, the preparation method of which comprises the following steps in sequence:

[0065] (1) In a nitrogen atmosphere, 1000 g of micron-sized silicon powder (D 50 ≤30μm) and 100g gallic acid and guar gum (1:1) were placed in 5.5L grinding solvent (ethanol) and ground with a sand mill to D 50 ≤50nm, nano silicon slurry is obtained;

[0066] (2) Add 10 g of nano-dispersant (DP-8300 and F-601 mixed in a mass ratio of 1:1) to the nano-silicon slurry, stir and mix, then add 150 g of acrylic resin soluble in the grinding solvent and stir evenly;

[0067] (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500° C. for 2 h under a nitrogen atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles;

[0068] (4) 1000 g of the coated precursor was added to the nano-silicon slurry diluted to a solid content of 20% by grinding solvent, and then 20 wt% of liquid asphalt was added, stirred evenly, sprayed and granulated for a second time, and then placed in a nitrogen atmosphere, calcined at 750 ° C for 5 h, and crushed and graded to D 50 The thickness of the carbon-coated silicon-based negative electrode material is 10 μm.

[0069] The particle morphology of the carbon-coated silicon-based negative electrode material after secondary spray granulation and crushing and classification in Example 1 is obtained, such as Figure 2 As shown. Among them, Figure 2 In the figure, from top to bottom are the morphology after secondary spray granulation and the morphology after crushing and classification.

[0070] At the same time, the carbon-coated silicon-based negative electrode materials obtained in Examples 1-7 and a blank control group (a sample in which pure silicon slurry without any carbon coating material was sprayed, calcined, and graded) were used to prepare electrode slurries, coated on a copper foil current collector, and sliced. After slicing, a metal lithium sheet was used as a counter electrode, and EC:DEC:DMC=1:1:1 was used as an electrolyte to assemble into 2032 button cells, and then the electrochemical performance was tested. The results are shown in Table 1.

[0071] Table 1 Electrochemical test results

[0072]

[0073] Depend on Figure 2 As shown in Table 1, after two spray granulation coatings, the specific surface area of ​​the final particles is significantly reduced, indicating that the coating method is effective. And from the data in the table, it can be seen that carbon coating can significantly improve the initial effect of the material. This is because carbon coating can not only physically protect silicon particles from erosion by the electrolyte, but also reduce the side reactions between silicon and active substances in the electrolyte through its chemical stability, further improving the initial effect of the battery.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-coated silicon-based negative electrode material, characterized in that: The following steps are included in sequence: (1) In an inert atmosphere, place micron-sized silicon powder and grinding aid in a grinding solvent and grind to D 50 ≤50nm, nano silicon slurry is obtained; (2) adding a nano-dispersant to the nano-silicon slurry, stirring and mixing, and then adding a long-chain resin material soluble in a grinding solvent, stirring evenly; (3) spraying and granulating the slurry in which the nano-silicon particles are evenly dispersed, and then calcining it at 500-1100° C. for 2-5 hours under an inert atmosphere to obtain a coating precursor in which the chain resin penetrates the nano-silicon particles; (4) Add the coated precursor to a nano-silicon slurry diluted with a grinding solvent to a solid content of 5-20%, then add 18-50wt% of liquid asphalt, stir evenly, spray granulate for a second time, and then place it in an inert atmosphere and calcine it at 500-1100°C for 2-5h. After crushing, grade it to obtain a carbon-coated silicon-based negative electrode material.

2. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (1), the mass volume ratio of silicon powder, grinding aid and grinding solvent is 1000g:100g:5.5L.

3. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (1), the grinding aid is at least one of lignin, gallic acid, tannic acid carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, gum arabic, gelatin and guar gum.

4. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (2), the mass ratio of the nano-dispersant to the long-chain resin material is 10g:150g.

5. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (2), the nano-dispersant is at least one of DP-8300, F-601, polyvinyl pyrrolidone and sodium dodecyl sulfate.

6. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (2), the long-chain resin material is at least one of acrylic resin, phenolic resin, polyvinyl butyral resin, polyurethane resin and natural resin.

7. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (3) and step (4), spray granulation is carried out at a temperature of 80-170°C.

8. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (4), after crushing, the mixture is graded to D 50 8-15μm.

9. The method for preparing a carbon-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (1) and step (4), the grinding solvent is at least one of ethanol, ethylene glycol and propylene glycol.

10. The carbon-coated silicon-based negative electrode material obtained by the method for preparing the carbon-coated silicon-based negative electrode material according to any one of claims 1 to 9.